The effectiveness of fluidotherapy in poststroke complex regional pain syndrome: A randomized controlled study - Sezgin Özcan, Didem; Tatlı, Hilmi Umut; Polat, Cemile Sevgi; Ayhan Öken, Öznur; Köseoğlu, Belma Füsun (Elsevier Science Bv, 2019)
Objective: To evaluate whether combining fluidotherapy to conventional rehabilitation program provides additional improvements on pain severity, upper extremity functions, and edema volume in patients with poststroke complex regional pain syndrome (CRPS). Design: Randomized controlled trial. Setting: Training and research hospital. Participants: Thirty hemiplegic patients with subacute stage CRPS type-1 of the upper extremity. Interventions: The patients randomly divided into 2 groups. Both groups received a 3 week conventional rehabilitation program (5 days/week, 2-4 hours/day). Experimental group received 15 sessions additional fluidotherapy application to the affected upper extremity (40 degrees C, 20 minutes in continuous mode, 5 sessions/week). Main Outcome Measures: We evaluated the distal upper arm edema with a volumeter. Other used clinical assessment scales were Brunnstrom recovery stages of the arm and hand for motor recovery, motor items of the functional independence measure for functional status, visual analog scale for pain severity, and the painDETECT questionnaire for presence and the severity of neuropathic pain. Results: The mean age of the participants was 64.3 +/- 11.66 (28-84). At the post-treatment evaluation, significant improvements were revealed regarding to the edema volume, pain visual analog scale, painDETECT and functional independence measure scores, and the Brunnstrom stages of upper extremity and hand in both groups (P <.05). But among the parameters mentioned above, only the decrease in edema volume and the painDETECT scores were greater in fluidotherapy group than the control group (P <.05). Conclusions: Addition of the fluidotherapy to the conventional rehabilitation program provides better improvements on neuropathic pain and edema volume in subacute stage poststroke CRPS.
WOS: 000469036700030
PubMed ID: 30940426
Keywords: Complex Regional Pain Syndrome; Fluidotherapy; Hand Volume; Hemiplegia; Neuropathic Pain; Physical Agents; Rehabilitation